Value Engineering on the Mosque Construction Project in the South Kalimantan Provincial Government Office Area - Yan Rahmatullah; Hanie Teki Tjendani; Budi Witjaksana (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2025)
The analysis performed to optimize costs will generate alternatives that will be compared with the initial design, and this analysis can be called value engineering analysis. This research aims to assess the percentage of cost savings that can be obtained by applying the value engineering technique, as well as to evaluate the life cycle cost of various selected material alternatives. The Mosque Construction Project in the South Kalimantan Provincial Government Office Area was chosen as the research object because of cost inefficiency in the architectural work, with a total cost of Rp. 26,857,215,362.63 out of the total project cost of Rp. 55,600,738,764.97. The architectural work will be corrected using Pareto diagram analysis through the value engineering phases, namely the information phase, speculation phase, and analysis phase. From the value engineering analysis results, a savings of 3.65% of the total project value was obtained. The life cycle cost analysis shows that the selected material has a lower life cycle cost value compared to the initially planned material. In addition, the work execution time with the selected material can complete the work on site more quickly